(untitled) - 1962-; Armentrout, David (Vero Beach, Fla., 1998)
Briefly describes the equipment, techniques, safety, laws and tournaments involved in both freshwater and saltwater fishing.
Includes bibliographical references (p. 24) and index.
Keywords: Fishing; Juvenile literature